Socio-economic and environmental impact of fisheries subsidies in Manjung, Perak - Noramiza, Mohd Salleh (2014)
Fisheries subsidies play a role as the aid incentive to the fisherman, especially to the small scale fishermen. However, subsidies to fishermen not allocated properly to fisherman who was supposed to receive it. The granting of fish subsidy should continue because it is able to contribute to the socio-economic improvement and fishermen to improve fishing catches in the fisheries activities carried out. The granting of this subsidy contributed to an increase in revenue the fishermen and help fishermen in terms of activities carried out. A study conducted to see the existing dimension relationship between socioeconomic and environmental for the fisherman in Manjung, Perak. The objective of this study was reviewed the subsidies given to fishermen as fuel subsidies and other incentives received fishermen, evaluating the notion of fishermen on fishing activities and the acceptance of subsidies and provide guidance in the future regarding fisheries subsidies towards sustainability and food security. The empirical model is used in this study to achieve the objective of the study by using the descriptive analysis and the multiple regression analysis. The result of the empirical analysis provided evidence of the relationship between the implementation of incentives, such as the fish catch incentive, the livelihood allowance subsides it has given the increase to income of fishermen. The study questionnaire fisherman perceptions fisheries subsidies for this study shows that all respondents are satisfied with the provision of incentives in the form of subsidy by the government. This implies that in the future in fisheries sector subsidies must be submitted as an incentive to fisherman and as policies that assist fisherman in Malaysia.